Prologue (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2017)
Benedek Elek Faculty of Pedagogy (University of Sopron) and the Faculty of Pedagogy (University of Kaposvár) organized the 10th Jubilee Training and Practice Conference at the University of Sopron on 27 April 2017. The motto of the conference was: “Diversity in National, International Educational Researches and in the Pedagogical Practice”. The present issue of our journal offers a selection of lectures delivered in German and English at the 10th International Jubilee Training and Practice Conference.